Dimethyl Fumarate Prevents the Development of Chronic Social Stress-Induced Hypertension in Borderline Hypertensive Rats - Michal Kluknavsky; Peter Balis; Silvia Liskova; Andrea Micurova; Martin Skratek; Jan Manka; Iveta Bernatova (MDPI AG, 2024)
This study investigated the effects of chronic crowding-induced social stress and dimethyl fumarate (DMF) on borderline hypertensive rats, focusing on the transcription nuclear factor (erythroid-derived 2)-like 2 (NRF2) gene Nfe2l2, on the expression of selected NFR2-mediated gene expressions in the heart, and on vascular function. Rats were exposed to chronic crowding, DMF treatment (30 mg/kg/day, p.o.), or a combination of both for six weeks. Blood pressure (BP) was measured non-invasively, gene expressions were analysed using RT-qPCR, and vascular function was assessed by measuring noradrenaline (NA)-induced vasoconstriction and endothelium-dependent and -independent relaxations in the femoral arteries using a wire myograph. Chronic stress increased BP, Nfe2l2 expression, and NA-induced vasoconstriction, though it did not affect relaxation responses nor the left heart ventricle-to-body weight (LHV/BW) ratio. DMF elevated Nfe2l2 expression (as the main effect) in the heart but did not alter BP and vascular functions vs. control when administered alone. Interestingly, DMF increased the LHV/BW ratio, supposedly due to reductive stress induced by continuous NRF2 activation. When combined with stress, DMF treatment prevented stress-induced hypertension and mitigated NA-induced vasoconstriction without altering relaxation functions. In addition, the combination of stress and DMF increased Tnf and Nos2 expression and the expressions of several genes involved in iron metabolism. In conclusion, these findings suggest that DMF can prevent chronic stress-induced hypertension by reducing vascular contractility. Moreover, DMF itself may produce reductive stress in the heart and induce inflammation when combined with stress. This indicates a need for the careful consideration of long-term DMF treatment considering its impact on the heart.